The predictive role of neutrophil-to-lymphocyte ratio in post-operative arrhythmias in pediatric patients after cardiopulmonary bypass surgery. (14th October 2021) - Bucciarelli, V; Bianco, F; Biasi, A; Primavera, M; Baldinelli, A; Colaneri, M; Gallina, S; Pozzi, M
Abstract: Background: Postoperative arrhythmias (POA) are a common complication after cardiac surgical repairs for congenital heart disease (CHD), representing a substantial source of morbidity, mortality and prolonged total in-hospital stay, with an incidence of 7.5–48% in postoperative pediatric cardiac patients. The etiology is multifactorial, and it has been related to the direct surgical manipulation of the cardiac conduction system, to the local tissue inflammation in the myocardium adjacent to the conduction system and to the arrhythmogenic effects of cardiopulmonary bypass (CPB), inotropes and electrolyte disturbances. Recently, the prognostic role of neutrophil-to-lymphocyte ratio (NLR), a novel inflammation marker, has been evaluated in pediatric patients after CPB surgery. Purpose: To evaluate the predictive role of NLR in POA in a population of pediatric CHD patients after CPB. Methods: We retrospectively collected perioperative clinical and laboratory data of 146 patients (age 8.27±10.79 years; male gender: 60.8%) consecutively admitted to the cardiac surgery intensive care unit (ICU) of our institute after elective cardiac surgery with CPB in 2018. We grouped and analyzed our population over NLR tertiles evaluated at 24 hours from CPB and types of POA: supraventricular (SVT) and junctional (JET). The prognostic value of NLR and its association with POA was analyzed. Results: Diagnoses of 146 patients included atrial septal defect (n=36), ventricular septal defect (n=20), pulmonary atresia/stenosis (n=10), tetralogy of Fallot (n=20), endocardial cushion defect (n=8), left ventricular outflow tract obstruction (n=14), anomalous origin of coronary artery (n=6), complex CHD (n=13), interrupted/hypoplastic aortic arch (n=12), anomalous pulmonary artery venous return (n=3). The mean CPB time was 121.6±84.6 minutes. The median ICU hospitalization was 48 hours [Q1, Q3: 24, 96]. Twelve patients experienced POA: 6 SVT and 6 JET. The frequency of POA incremented over NLR-tertiles (P-Trend 0.017), while SVT onset was associated with higher values of NLR and C-reactive protein (P=0.034 and P=0.011, respectively). Patients in the second and third tertiles of NLR had a prolonged hospitalization (Log-rank, P=0.029), especially when associated with POA (Log-rank, P=0.012). At the multivariable analysis, higher age and NLR values were independently associated with SVT [OR per year 1.22; 95% CI (1.02, 1.25), P=0.043 and OR per point 1.91; 95% CI (1.29, 2.82), P=0.012, respectively], but not with JET. Conclusions: 24-h post-CPB NLR can predict postoperative SVT in a population of pediatric CHD patients. Our data suggest that the NLR could be a useful, easy-to-obtain marker for postoperative outcome in pediatric patients who had undergone elective CPB. FUNDunding Acknowledgement: Type of funding sources: None.